The biopsychological analysis. (Journal of Parents and Teachers, 2025)
The article states that biopsychological analysis is a holistic approach to understanding the human being, encompassing a unified view of all its dimensions. It is also an approach that prioritizes the body during the therapeutic process, where muscular tensions should be relaxed, and attention given to the quality of presence, the integration of body and mind, and the opening of the senses and heart.